A fast transient FVF-based output capacitorless LDO with self-feedback biasing. (April 2023) - Liu, Nan; Xie, Yiling; Guo, Jianping
Abstract: An improved flipped voltage follower (FVF) based output-capacitorless low-dropout regulator (OCL-LDO) with self-feedback biasing has been proposed in this paper, achieving better performance without increasing the number of transistors or adding complicated circuits for the customized transient performance. With the proposed self-feedback biasing technique, the equivalent transconductance of the error amplifier is boosted effectively, so that the DC gain of the proposed FVF-LDO is increased and thus both the load and line regulations are improved. At the same time, the dynamic bias current is generated to enhance the transient response. In addition, a single-transistor-based fast discharge loop is added to further enhance the transient response. The proposed OCL-LDO has been designed and fabricated in 180-nm CMOS technology. The chip area is 0.017 mm 2, and the measured quiescent current is 79 μ A. The proposed LDO can be stable with 0 ∼ 100-pF output capacitance under current ranges from 0 ∼ 100 mA, and the FoM is as small as 0.0036 ps when loading current changes from 0 to 100 mA.